Lebanon : Use of Fund Resources; Request for Emergency Post-Conflict Assistance; Staff Report; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2008)
The Lebanese authorities have requested follow-up Emergency Post-Conflict Assistance with an access of 12.5 percent of quota to support their economic program. The 2006 war with Israel led to a political stalemate and repeated outbreaks of domestic fighting until the formation of a national unity government in July 2008. Macroeconomic conditions have improved, but fuel and food prices have boosted inflation. Financial market developments have been favorable, despite the global financial crisis, which has had little effect on Lebanon.